Reading Instructional Model Using Novel in Cooperative Learning for Senior High School Students - Desy Puspitasari; Dwijani Ratnadewi; Waode Hamsia (Tell : Teaching of English Language and Literature Journal, 2014)
English is very important to be learned by the people, because English as an international language widely used by society. This research describes the implementation and the studentâ€™s response after the teacher teaching reading novel for eleventh grade students at SMA GEMA 45 Surabaya. In this research, the researcher observed when the teacher teaching reading â€œSilas Marnerâ€ novel using cooperative learning techniques. This research aims to describe the implementation and the studentâ€™s responses after the teacher teaching reading for eleventh grade students at SMA GEMA 45 Surabaya. This research uses descriptive qualitative research. To collect the data, the researcher used three kinds of instruments they are: interview, observation and questionnaire. The teacher used jigsaw and number heads together to teach reading â€œSilas Marnerâ€ novel in each meeting. The results show that after the teacher teaching reading, the students have achievement in two aspects; speaking aspect and writing aspect. Besides that, through teaching reading novel using jigsaw and number heads together can help the students easy to comprehend â€œSilas Marnerâ€ novel and it can avoid studentâ€™s bore. Furthermore, the teacher should apply appropriate technique for the students who need to increase critical thinking when the students studying at class.